2012
DOI: 10.1155/2012/462967
|View full text |Cite
|
Sign up to set email alerts
|

Present Status and Perspectives on the Use of Alkylresorcinols as Biomarkers of Wholegrain Wheat and Rye Intake

Abstract: Alkylresorcinols (ARs) were first proposed as potential biomarkers of wholegrain wheat and rye intake a decade ago. Since then there has been a considerable body of research which suggests that ARs do meet most criteria of a biomarker of these foods. Results from human studies on plasma AR and their plasma and urinary metabolites strongly indicate that these compounds are responsive to whole grain wheat and rye intake and are correlated with various measures of AR consumption. This review briefly summarises wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 89 publications
9
92
0
6
Order By: Relevance
“…Although several studies have related estimates of wholegrain intake to concentrations of plasma AR (5,12,16,17,27,32), most of these studies were conducted in adults living in northern Europe where habitual whole-grain intake may be higher than in the United States (daily consumption <16 g or 1 serving) (33). For example, the mean intake of whole grains in a general Danish population was ;35 g/d (;2 servings) (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have related estimates of wholegrain intake to concentrations of plasma AR (5,12,16,17,27,32), most of these studies were conducted in adults living in northern Europe where habitual whole-grain intake may be higher than in the United States (daily consumption <16 g or 1 serving) (33). For example, the mean intake of whole grains in a general Danish population was ;35 g/d (;2 servings) (12).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the correlation coefficient between plasma AR and whole-grain wheat-based foods was 0.31. In other studies, reported correlation coefficients between plasma AR concentration and whole-grain intake ranged from 0.25 to 0.58, depending mostly on the dietary assessment tool used but also on study population, sample size, and type of study (i.e., observational or intervention) (27). In a large cohort of overweight participants undergoing a whole-grain-based intervention in the United Kingdom, the correlation between plasma AR and estimates of whole-grain intake derived from a general diet FFQ was 0.36.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic concentrations varied from 10 -4 M to 10 -7 M, which corresponded to the experimentally-detected presence of HSLs and RLs in biological liquids and tissues of humans [5,6].…”
Section: Chemicalsmentioning
confidence: 79%
“…The RLs are synthesised by some pro-and eukaryotes [3] and operate as inductors of bacterial cell transition into the dormant stage [4]. On the other hand, these amphiphilic substances diffuse easily through epithelial barriers into human liquids and tissues where experimentally detected HSLs and RLs concentrations vary from nano-to micro-molar [5,6]. As a result, HSLs affect the function of a wide range of mammalian cell types (including cells of the immune system), repress the production of DOI: 10.5114/ceji.2013.37752 cytokines, disrupt the function of antigen-presenting cells [7,8], and alter cell metabolism and cycling [9].…”
Section: Introductionmentioning
confidence: 99%